Pengembangan Aplikasi Pemesanan Menu Café dengan Metode Agile - winanti, winanti; Darmawan, Dwiky; Yusuf, Yusuf; Tama, Ardy Riyantai; Widiyanti, Dian; Sa’adah, Fitria; Septian, Indra; Basuki, Sucipto; Jumiran, Jumiran; Nurasiah, Nurasiah (Universitas Wahid Hasyim, 2025)
The ordering system at Café XYZ is still carried out conventionally where customers must come directly to the café so that service is slow if there is a long queue. The purpose of developing a Café menu ordering application is to simplify and speed up the café menu service and check order reports that can be done in real time. The data collection method is carried out by direct observation at Café XYZZ. The application development uses the Agile method, and a website-based system. Application testing is carried out using black box testing by testing the ease of use of the application and the completeness of the features. The cafer menu ordering application really helps customers in ordering menus and makes it easier for admins in terms of reporting and can reduce the length of the queue. The application will be developed in the future on a mobile basis to provide better service and convenience to customers